1985
DOI: 10.1203/00006450-198504000-01841
|View full text |Cite
|
Sign up to set email alerts
|

1823 Ceruloplasmin (Cer) Levels in Prematures at Risk for Bronchopulmonary Dysplasia (Bpd)

Abstract: Twenty two c h i l d r e n (age range :3-14 years, Sex:m:f: :12:lO) adm i t t e d t o Kings County H o s p i t a l o f Brooklyn w i t h s t a t u s asthmaticus were s t u d i e d t o determine t h e i r plasma ADH l e v e l s i n r e l a t i o n t o the s e v e r i t y o f the s t a t u s asthmaticus. Plasma ADH l e v e l s were measured b y RIA a t t h e time o f admission and again a t 1-2 weeks f o l l o w i n g recovery from s t a t u s . The r e s u l t s are shown i n t h e table.We conclude from t h e s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…These exclusion criteria were chosen because previous investigations could demonstrate significantly lower serum transferrin and/or ceruloplasmin concentrations in prematures suffering PIVH or BPD [4,5]. Finally, 63 premature newborns remained in the study group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These exclusion criteria were chosen because previous investigations could demonstrate significantly lower serum transferrin and/or ceruloplasmin concentrations in prematures suffering PIVH or BPD [4,5]. Finally, 63 premature newborns remained in the study group.…”
Section: Methodsmentioning
confidence: 99%
“…The role of free ionic iron (Fe 2+ ) in the generation of oxygen free radicals as well as the antioxidative properties of ceruloplasmin (oxidation of Fe 2+ → Fe 3+ ) and transferrin (ligation of Fe 3+ ) thereafter have been the subject of many investigations. These studies suggest that either increased serum iron concentrations and/or decreased serum transferrin and ceruloplasmin levels may be associated with the development of radical-induced diseases of prematurity, e.g., retinopathy of prematurity (ROP), periventricular-intraventricular hemorrhage (PIVH), bronchopulmonary dysplasia (BPD) or necrotizing enterocolitis (NEC) [3][4][5]. To identify a premature newborn possibly at risk for the development of such a disorder, gestational age-dependent reference ranges of these laboratory values are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown reduced A1PI functional activity [3][4][5][6][7] or higher tracheal elastase activity [5][6][7][8][9] in preterm babies who later developed CLD compared to those who did not. Based on these and other observations, it was hypothesized that treatment of premature babies with A1PI would result in augmentation of antiprotease activity, inhibition of neutrophil elastase activity and protection from the development of CLD.…”
mentioning
confidence: 99%
“…Infants who develop BPD have a 20-fold increase in the neutrophil infl ux [54] and an imbalance between proteases and antiproteases [83] . A low functional level of α 1-protease inhibitor at birth may predict BPD development [68] , but in an RCT of neonates aged < 24 h, with birth weights between 600 and 1000 g, and requiring respiratory support or with birth weight between 1001 and 1250 g and with RDS, supplementation did not result in a signifi cant reduction in BPD, but there was a lower incidence of pulmonary haemorrhage [83] .…”
Section: Antioxidantsmentioning
confidence: 99%